2012
DOI: 10.1111/jonm.12005
|View full text |Cite
|
Sign up to set email alerts
|

An integrative review of spiritual assessment: implications for nursing management

Abstract: The issues to emerge from this paper are (1) that spiritual assessment is an increasingly important issue for nursing practice, (2) that the range of reliable and valid quantitative instruments for use in clinical practice is limited, (3) that there is overlap in the domains and categories of spirituality identified by quantitative and qualitative researchers, and (4) that nurse managers seeking to introduce spiritual assessment will do so in the context of a professional debate about the relevance of spiritua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 60 publications
0
26
0
6
Order By: Relevance
“…4,19,38,48,49 Every known spiritual needs assessment instrument was (much) more elaborate than necessary for our purposes. We finally decided to take the 2 spiritual questions from the Dutch Distress Thermometer as our starting point.…”
Section: Genesis Of the Spiritual Historymentioning
confidence: 99%
See 2 more Smart Citations
“…4,19,38,48,49 Every known spiritual needs assessment instrument was (much) more elaborate than necessary for our purposes. We finally decided to take the 2 spiritual questions from the Dutch Distress Thermometer as our starting point.…”
Section: Genesis Of the Spiritual Historymentioning
confidence: 99%
“…4,6,19,[37][38][39][40] At the same time, various studies indicate that patients themselves report that attention for spirituality in their medical history is important. 3,26,37 In spite of the existing attention for a spiritual needs assessment, no research-that we could find-has been conducted into its effects.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Rather than nurses, Draper suggests that a generic model of the FICA [7,8] should be used to initially screen the spiritual status of patients [6], and that spiritual needs of patients should be further assessed according to four categories: 1) meaning, purpose, and hope; 2) relationship with God; 3) spiritual practice, religious obligation, and interpersonal connection; and 4) professional staff interactions [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Draper conducted an integrative review of spiritual assessment and identified three categories: generic, quantitative [6], and qualitative approaches and conducted a metasynthesis of all approaches. The author recommends that spiritual assessment should start from a generic model such as the FICA model [7,8].…”
Section: Spiritual Assessmentmentioning
confidence: 99%